(NiZBRANNYE SO^INENIQ W DWUH TOMAH (B/s (N~ASTX (B1s - (NpU[KIN(B, (NaLEKSANDR sERGEEWI^s ((NmOSKWA(B:s (NhUDOVESTWENNAQ LITERATURA(B,s, 1978)
(Nw PERWYJ TOM SO^INENIJ a(B.(Ns(B. (NpU[KINA WO[LI IZBRANNYE STIHOTWORENIQ(B, (NPO\MY I SKAZKI(B.s
rus
Keywords: (NsTIHOTWORENIQs; (NpO\ZIQ(B, (NPO\MYs; (NrUSSKAQ LITERATURAs